PhiloLogic4: An Abstract TEI Query System - Timothy Allen; Clovis Gladstone; Richard Whaling (Journal of the Text Encoding Initiative)
A common problem for TEI software development is that projects develop their own custom software stack to address the semantic intricacies present in a deeply-encoded TEI corpus. This article describes the design of version 4 of the PhiloLogic corpus query engine, which is designed to handle heterogeneous TEI encoding through its redesigned abstract data model. We show that such an architecture has substantial benefits for software reuse, allowing for powerful TEI applications to be adapted to new corpora with a minimum of custom programming, and we discuss the more general and theoretical implications of abstraction as a TEI processing technique.